Deep Brain Stimulation to Alleviate Freezing of Gait and Cognitive Dysfunction in Parkinson's Disease: Update on Current Research and Future Perspectives - Huang, Chuyi; Chu, Heling; Zhang, Yan; Wang, Xiaoping (Frontiers in Neuroscience, 2018)
Freezing of gait (FOG) is a gait disorder featured by recurrent episodes of temporary gait halting and mainly found in advanced Parkinson’s disease (PD). FOG has a severe impact on the quality of life of patients with PD. The pathogenesis of FOG is unclear and considered to be related to several brain areas and neural circuits. Its close connection with cognitive disorder has been proposed and some researchers explain the pathogenesis using the cognitive model theory. FOG occurs concurrently with cognitive disorder in some PD patients, who are poorly responsive to medication therapy. Deep brain stimulation (DBS) proves effective for FOG in PD patients. Cognitive impairment plays a role in the formation of FOG. Therefore, if DBS works by improving the cognitive function, both two challenging conditions can be ameliorated by DBS. We reviewed the clinical studies related to DBS for FOG in PD patients over the past decade. In spite of the varying stimulation parameters used in different studies, DBS of either subthalamic nucleus (STN) or pedunculopontine nucleus (PPN) alone or in combination can improve the symptoms of FOG. Moreover, the treatment efficacy can last for 1-2 years and DBS is generally safe. Although few studies have been conducted concerning the use of DBS for cognitive disorder in FOG patients, the existing studies seem to indicate that PPN is a potential therapeutic target to both FOG and cognitive disorder. However, most of the studies have a small sample size and involve sporadic cases, so it remains uncertain which nucleus is the optimal target of stimulation. Prospective clinical trials with a larger sample size are needed to systematically assess the efficacy of DBS for FOG and cognitive disorder.